Возраст заключительной фазы магматизма в позднем докембрии на Волыни по новым геохронологическим и палеомагнитным данным - Кравченко, С.Н. (Видавничий дім "Академперіодика" НАН України, 2007)
Based on an interdisciplinary analysis of the new geochronological and palaeomagnetic information on the magmatic and sedimentary rocks from Volyn and Podoliya, the upper age constraint (545 Ma) is obtained on the termination of volcanic activity in the Late Precambrian of this region. It practically coincides with the end of basaltic volcanism (551 Ma) in the adjacent area of the eastern Poland. In both regions, this magmatism is related to the opening of the Iapetus Ocean.